Pengaruh Kualitas Audit, Komite Audit, Kepemilikan Institusional, Ukuran Perusahaan, dan Leverage Terhadap Manajemen Laba - Riani, Desmy; Rumiasih, NA.; Sundarta, M. Imam; Lili, Muhamad (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
AbstractThis study aimed in determining the effect of audit quality, audit committee, institutional ownership, company size, and leverage on earnings management in banking companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. This study used secondary data in the form of annual financial statements of banking companies for the period 2015-2019. Was used in this study sampling technique used in the study was purposive sampling and the number of samples used were 35 banking companies with a research period of 5 years. Analysis of the date in the study were using multiple linear regression analysis using SPSS25 and Eviews6 software. The results showed that the audit quality variable and the audit committee variable had no significant effect on earnings management. Furthermore, the institutional ownership and leverage had a significant positive effect on earnings management. Meanwhile, the firm size variable had a significant negative effect on earnings management. Simultaneous research resulted the consisting of audit quality, audit committee, institutional ownership, company size and leverage had a significant positive effect on earnings management.